ETIKA PERJUANGAN MASYARAKAT JEPANG - Sri Sudarsih (KIRYOKU, 2017)
Japan is a country in Asia which is interesting to review. The purpose of this paper is to find ethically of Japan Society struggle in building the nation and the state. The ethics of the struggle of Japan pulling studied because the struggle the people of Japan have reached a goal that is being developed and prosperous.This paper is a study of librarianship. The material object in this paper is the struggle of life society Japan, while the formal object is ethics. The method used is a  description and interpretations.The key to success in the construction began of building the individual responsible and strict norms. A shame for the people of Japan into energy to act right. Failure to achieve the expectations of perceived as failure to maintain the norm.  This means that the same failure with dereliction of duty so feel have no self-esteem. A person's self-esteem is reflected in the existence of responsibility, think, act, and work correctly.